How natural is the supernatural? Synthesis of the qualitative literature from low and middle income countries on cultural practices and traditional beliefs influencing the perinatal period. (August 2016) - Raman, Shanti; Nicholls, Rachel; Ritchie, Jan; Razee, Husna; Shafiee, Samaneh
Abstract: Objective: to review qualitative research studies conducted in low resource settings around the perinatal continuum over the past two decades, with particular focus on the cultural realm; to identify common themes in the research-base, in order to provide policy direction for culturally appropriate perinatal interventions. Design: systematic literature search of electronic databases from 1990 to 2014, including Medline, Embase, CINAHL and PsycINFO, using relevant search terms such as traditional beliefs, practices, pregnancy, childbirth; established criteria used to determine quality of studies; and thematic synthesis of the literature enabled by NVivo 10 software. Setting: low and middle income countries using the World Bank classification. Findings: religious and spiritual beliefs strongly influenced behaviour over the perinatal period. Beliefs in supernatural influences, particularly malevolent forces were widespread, such that pregnancy was concealed in many parts of Africa and Asia. In most low resource settings, pregnancy and childbirth were seen as normal phenomena. Rituals played an important part for women and their infants, reinforced by inter-generational support. Cross-cutting themes that emerged were: (1) the role of women as mothers, demonstrating their'goodness' by bearing pain and suffering; (2) the idea of the 'natural' incorporating the supernatural; and (3) negotiating change across generations. Conclusions and implications for practice: a diverse repertoire of cultural practices influences perinatal well-being across low resource settings. Health practitioners and policy-makers need to acknowledge the primacy of women's reproductive roles, the cultural constructions of motherhood; that supernatural forces are believed to exert powerful influences on the health of mother and infant; that inter-generational tensions result in resisting or embracing change. Public health planners and practitioners need to take culture seriously, not ignore the contribution of culture in shaping women's behaviours and choices throughout the perinatal continuum and deliver contextually specific, culturally responsive care to optimise perinatal health and well-being. Highlights: A rich repertoire of cultural practices pervades the perinatal period in low resource settings. Strong beliefs in supernatural forces persist, yet pregnancy, childbirth are considered natural. Ritual is important throughout the perinatal period, maintained and reinforced by elders. A dominant underlying theme is the role of the woman as strong, capable of bearing intense suffering. Although change is evident, there are tensions between incorporating and resisting change.